2016
DOI: 10.1016/j.jcat.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective in the Use of FeOx-TiO2 Photocatalytic Films: Indole Degradation in the Absence of Fe-Leaching

Abstract: The first evidence is reported for the degradation of Indole at the solid air interface under low intensity solar simulated light in a stable repetitive fashion. The cosputtering of FeOx-TiO 2 on polyethylene (PE) lead to an accelerated Indole degradation kinetics compared to TiO 2-PE and FeOx-PE films. Indole degradation on TiO 2-PE, FeOx-PE and polyethylene (PE) supported photocatalysts is shown to proceed without Fe-or Ti-release as detected by inductively coupled plasma mass-spectrometry (ICP-MS). This ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Rtimi et al recently reported the first evidence of the Cu and Ti nanoparticles mapping and distribution on the film surface as detected by wavelength dispersive spectrometry (WDS). They showed the correlation between the surface microstructure and the bacterial inactivation kinetics for the two composite catalyst preventing biofilm formation [55]. For better understanding of the notation, in the present review, we will use CuO x /TiO 2 for sequentially sputtered surfaces and TiO 2 -CuO x for co-sputtered surfaces.…”
Section: Cu Coupled With Tio 2 Sputtered Surfaces Active In the Visibmentioning
confidence: 99%
See 1 more Smart Citation
“…Rtimi et al recently reported the first evidence of the Cu and Ti nanoparticles mapping and distribution on the film surface as detected by wavelength dispersive spectrometry (WDS). They showed the correlation between the surface microstructure and the bacterial inactivation kinetics for the two composite catalyst preventing biofilm formation [55]. For better understanding of the notation, in the present review, we will use CuO x /TiO 2 for sequentially sputtered surfaces and TiO 2 -CuO x for co-sputtered surfaces.…”
Section: Cu Coupled With Tio 2 Sputtered Surfaces Active In the Visibmentioning
confidence: 99%
“…A big difference was also seen between sequentially sputtered CuOx/TiO2 (Figure 8, trace 2) and co-sputtered CuOx-TiO2 (Figure 8, trace 3) with respect to HIPIMS sample (Figure 8, trace 1). The band-gap positions [55][56][57] enable the electronic hole injection from CuO to TiO 2 limiting electron/hole recombination in the CuO and permit the TiO 2 holes (h + ) to inactivate bacteria. The interfacial charge transfer (IFCT) to TiO 2 from the CuO vb at +1.4 eV to the TiO 2vb at +2.5 eV vs. SCE was senn to be favorable.…”
Section: Cu Coupled With Tio 2 Sputtered Surfaces Active In the Visibmentioning
confidence: 99%
“…The degradation rate of RhB decreased dramatically, further confirming the importance of the ·O 2 − active species generated from the O 2 molecules. Combined with the band gap of the nanocomposite, the possible photocatalytic mechanism of the Fe 3 O 4 /TiO 2 composite is described in Scheme 2 [17]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, magnetic titania has gained increasing attention, as it has the advantages of magnetic recovery and excellent photocatalytic properties [15,16,17,18,19]. They can achieve the fast separation and easy recovery of nano-TiO 2 by external magnetic fields, thus preventing the loss of active components and improving the durability of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Binary-oxides semiconductors due to their optical absorption and semiconductor behavior have been widely used for environmental decontamination purposes like FeOx-TiO 2 . These binary oxides play an important role in pollutants and bacterial abatement involving redox processes [ 72 , 73 ]. Supported photocatalyst films, for self-cleaning and self-sterilizing purposes have recently been developed.…”
Section: Coupling Of Tio 2 and Fe-oxide: Innovamentioning
confidence: 99%